PERANCANGAN DASHBOARD UNTUK MEMANTAU KINERJA DOSEN FAKULTAS TEKNOLOGI INFORMASI DI UNIVERSITAS TARUMANAGARA - Apostel Horeb (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
In every organization, it should be able to manage all processes quickly. Therefore, the institution monitors the entire process of lecturer performance so that it can achieve benefits and improve quality. This Dashboard design uses the prototyping method, by observing this information we can create a Web-based Dashboard to monitor the performance of the Faculty, using the UML method in system design and using mySql and Xampp to create a web-based Dashboard visualization. The results of making this Dashboard can provide ease in monitoring the overall performance of the FTI Faculty.